The views of the leaders of the New Age movement on traditional religion (Przegląd Religioznawczy – The Religious Studies Review, 2020)
This article presents how religion and its role in human life were understood by the creators of the doctrine of the New Age movement. Due to the fact that the New Age movement lacked formal structures and codified teachings, I demonstrate the views expressed by leading figures who contributed towards the doctrinal basis of this movement. They were: Marilyn Ferguson, Fritjof Capra, and David Spangler. I also refer to the authors from outside of the ranks of the New Age activists whose works became important sources of inspiration for the New Age doctrine. I present their main propositions regarding the nature and function of religion, as well as the end-purpose of its existence. However, in the course of the analyses of the views of those authors it was not always possible to ascertain whether they spoke of religion as such or one of its specific forms which is Christianity. So, I first discuss their position on problems caused, according to them, by the fact that religion is one of the fundamental elements of culture, and then, in the second part of this article, I reconstruct their views regarding one particular religion: Christianity.